POPULATION DYNAMICS OF RHIZOSPHERIC AND ENDOPHYTIC BACTERIA IN CULTIVATION OF CILEMBU SWEET POTATO (Ipomoea batatas var. cilembu) AND THEIR ROLES DURING STORAGE OF POSTHARVEST - Monalisa Tangapo, Agustina
Cilembu sweet potato (Ipomoea batatas var. cilembu) is one of the superior varieties of sweet potato which originated from Cilembu Village, Sumedang, West Java, Indonesia. Due to its honey-like sweet taste after roasted, Cilembu sweet potato becomes well-known and thus become an export commodity. As the land to cultivate it in Cilembu Village decreases and the extensification of growing it outside its origin area, the production of Cilembu sweet potato generates different qualities of sweet taste. The uniqueness of this commodity is not only generated by both its variety factors and the specified area of its growth, but also by the storage treatments after harvest before consumption. During storage, starch degradation by enzymes in both plants and its endophytic bacteria causes changes in the sugar contents of the produce. Endophytic bacteria can be colonized from rhizospheric bacteria that are specific to its host plants and environment, and therefore will also be specific to the environment in which the host plants grow. The utilization of bacterial communities associated with Cilembu sweet potato from its origin region can be used as an alternative approach to increase the productivity of this commodity through the extensification of growing it outside its origin area and still maintain its unique qualities. The dynamics of bacterial communities associated with Cilembu sweet potato was examined by the abundance and diversity of culturable bacteria, as well as the diversity of substrate utilization using Biolog EcoPlate. During the growth of Cilembu sweet potato, 40 isolates were successfully isolated from the rhizosphere and a total of 22 isolates were isolated from the endophytic bacterial communities. These isolates include Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes phyla. Isolates identified as rhizospheric bacteria were also found as endophytic bacteria. The abundance of rhizospheric and endophytic bacteria communities was significantly different during the five months of growth. The abundance of rhizospheric bacteria during the first two months after planting reached 1.31x108 cfu/g, higher than last three months of growth (6.4x107–6.7x107 cfu/g). For endophytic bacteria, the highest abundance was observed in three months old tubers (1.15x105 cfu/g), but it was not significantly different with the abundance observed in the two months old tubers (1.04x105 cfu/g). Total metabolic activity observed using the average well color development (AWCD) iv indicates that rhizospheric bacterial communities had higher metabolic activities than endophytic bacteria, with highest AWCD observed in samples with the highest density of culturable bacteria for both rhizospheric and endophytic bacterial communities. Substrates utilization by rhizospheric bacterial communities at the initial and intermediate growth stages were positively correlated with carbohydrates, carboxylic acid and amino acid. The activities of endophytic bacteria were high in carbohydrate utilization during growth stages, especially at the intermediate until the final stage of tuber development. Isolates potential analysis were examined for plant growth-promoting (PGP) traits, including production of IAA (indole acetic acid), nitrogen fixation, ammonification, phosphate solubilization, cellulolytic and amylolytic activities. In rhizosphere bacteria communities, Klebsiella pneumoniae and Enterobacter cloacae were dominant in the first two months of growth and have the ability to promote plant growth using direct mechanisms that produces IAA, nitrogen fixation, ammonification and phosphate solubilization. During the final stages of growth, the dominance of Bacillus was increased. In endophytic bacteria communities, E. cloacae and Bacillus subtilis were dominant during the first month after planting. The dominance of E. cloacae continued until the tubers formed (2–3 months after planting), while a few of genus Bacillus were dominant until the last stages of growth like they were in the rhizospheric bacteria communities. The isolation of endophytic bacteria in Cilembu sweet potato during five-week storage period showed total bacterial abundance of 7.15x104–2.77x105 cfu/g, with the density of amylolytic bacteria reached 5.4x104 cfu/g. There were eight endophytic bacteria isolates exhibiting activities of amylase, which hydrolyze starch during storage. These isolates include Bacillus subtilis, B. mojavensis, B. megaterium, B. licheniformis, B. amyloliquefaciens, B. mycoides, B. safensis and Staphylococcus haemolyticus. In this study, it is confirmed that the inoculation of endophytic bacteria B. subtilis and B. amyloliquefaciens before storage changes the composition of sugar during storage of Cilembu sweet potato. Changes occurred were observed in glucose and fructose level increase (2.12% and 1.62% respectively), achieved after one week of storage, faster than control samples (without bacterial inoculation, 1.58% of glucose and 1.12% of fructose after four weeks of storage). These increases occurred along starch and sucrose decreases in the inoculated samples. Results obtained in this study can be further used as the basis for subsequent developments in field applications of bacterial communities associated with the origin grow region of Cilembu sweet potato.